TOWARD COMMUNITY-BASED WAQF INVESTMENT TO EMBODY EDUCATIONAL INSTITUTIONS FOR ELEMENTARY SCHOOLS AS A PUBLIC SPHERE - Shulhan, Shulhan (Kodifikasia, 2024)
The paper discussed critical issues related to community-based waqf practices to strengthen education services. This research was intended to fill the gap in the idea of systematically organized community waqf practices by educational institutions. It from a specific community, such as parents, is collected, structured, and timed to increase the amount of its funds. In addition, the issue of waqf for education has revolved chiefly around higher education, and very few have touched on the primary and secondary education levels. Talal Asad's view on the position of agency that has a vital role in religion was used to discuss the above topic. This research used a qualitative method based on a literature study by placing academic texts as data sources. Data analysis used content analysis with the stages of collection reduction and verification. The results are mentioned in the following. First is the waqf action movement for education, which positions the foundation manager as the initiator, actor, activator, developer, manager, and person in charge. Second, the collected waqf funds are invested into strategic and low-risk economic activities, such as real estate and business ventures, carefully selected to ensure stable and sustainable returns. These profits are then utilized for educational activities such as teacher salaries, operations, and the development of learning facilities